Gloriously Good Whole Grains - Paula G. Harris; Karla P. Shelnutt (EDIS)
You know they are good for you and that you should eat more of them, but have you ever really wondered what “whole grains” are and why they are important? If you have, you probably are not alone. Would you like to know if all grains created equal or how to tell the difference between a refined grain and a whole grain? Well, look no further. This 3-page fact sheet will answer your questions about whole grains and help you understand what makes whole grains so glorious. Written by Paula G. Harris and Karla P. Shelnutt and published by the UF Department of Family Youth and Community Sciences, April 2011.